2021
DOI: 10.1186/s12885-021-09003-z
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and outcomes of immune-related adverse events in solid tumor patients treated with immune checkpoint inhibitors in Thailand: a multicenter analysis

Abstract: Background Most immune-related adverse event (irAE) patterns and treatment guidelines are based on western clinical data. We evaluated the incidence and patterns of irAEs in patients treated with immune-checkpoint inhibitors (ICI) in Thailand. Methods All solid tumor patients treated with ICIs were retrospectively reviewed in a multicenter analysis. The study aims to evaluate the incidence of irAEs and their characteristics, treatments, outcomes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
3
4
1
Order By: Relevance
“…The relationships of irAEs onset and prognosis have been studied previously. [12][13][14] In line with previous studies, we found that patients with irAEs onset would achieve better prognosis than patients without irAEs, in the aspect of PFS and OS. Furthermore, we demonstrated that onset of skin toxicities would indicate a better PFS, which is also consistent with other studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The relationships of irAEs onset and prognosis have been studied previously. [12][13][14] In line with previous studies, we found that patients with irAEs onset would achieve better prognosis than patients without irAEs, in the aspect of PFS and OS. Furthermore, we demonstrated that onset of skin toxicities would indicate a better PFS, which is also consistent with other studies.…”
Section: Discussionsupporting
confidence: 91%
“…The relationships of irAEs onset and prognosis have been studied previously 12–14 . In line with previous studies, we found that patients with irAEs onset would achieve better prognosis than patients without irAEs, in the aspect of PFS and OS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although our landmark analysis did not fully resolve the immortal bias, by excluding patients with survival periods shorter than 3 months in the present study, this underling bias was reduced, thereby strengthening our findings. Three months seemed to be long enough as the setting of landmark because the median time of onset of overall irAEs is about 2 months, and majority of irAEs appears within 3 months, as previously reported 22,23 . The results were similar when the analysis was limited to patients who survived more than 6 months.…”
Section: Discussionsupporting
confidence: 72%
“…Three months seemed to be long enough as the setting of landmark because the median time of onset of overall irAEs is about 2 months, and majority of irAEs appears within 3 months, as previously reported. 22,23 The results were similar when the analysis was limited to patients who survived more than 6 months. To further emphasize the significance of irAEs as a predictor of efficacy to pembrolizumab, a sensitivity analysis was also performed.…”
Section: Discussionmentioning
confidence: 67%